2015
DOI: 10.1371/journal.pone.0136640
|View full text |Cite
|
Sign up to set email alerts
|

The Role of End-of-Life Issues in the Design and Reporting of Cancer Clinical Trials: A Structured Literature Review

Abstract: BackgroundRandomized controlled trials (RCTs) are important sources of information on the benefits and harms patients may expect from treatment options. The aim of this structured literature review by the German Institute for Quality and Efficiency in Health Care was to explore whether and how the end-of-life (EoL) situation of patients with advanced cancer is considered in RCTs investigating anti-cancer treatments.MethodsOur journal pool comprised 19 medical journals, namely five preselected key general medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
2
0
2
Order By: Relevance
“…First, this may be part of tradition and routine. It has been found that RCTs on cancer therapies still avoid the use of palliative or even end-of-life terminology, seldomly mentioning or discussing the limited life-expectancy and QoL needs of the patients, even in patient populations where life expectancy is less than one year (25). Second, the routine monitoring of PROs has not yet become common practice in many cancer care settings, even though this is encouraged by guidelines, patient advocates and evidence-based findings (17,26,27).…”
Section: Findings From the Recent Systematic Review By Fabian Et Almentioning
confidence: 99%
“…First, this may be part of tradition and routine. It has been found that RCTs on cancer therapies still avoid the use of palliative or even end-of-life terminology, seldomly mentioning or discussing the limited life-expectancy and QoL needs of the patients, even in patient populations where life expectancy is less than one year (25). Second, the routine monitoring of PROs has not yet become common practice in many cancer care settings, even though this is encouraged by guidelines, patient advocates and evidence-based findings (17,26,27).…”
Section: Findings From the Recent Systematic Review By Fabian Et Almentioning
confidence: 99%
“…Por lo tanto, las restricciones en su vida cotidiana se exponen a través de una baja capacidad funcional, mental, social y espiritual, que requieren de una atención activa e integral con el objetivo de mejorar la calidad de vida 11 . En este sentido, se reconoce el beneficio terapéutico de prolongar la vida, mediante la reducción de síntomas físicos, relacionados con el paradigma de enfermedad para el final de la vida 12 .…”
Section: Impacto De Los Cuidados Paliativos En La Calidad De Vidaunclassified
“…Las tasas de respuesta están alrededor del 20%, con supervivencia media de 6 a 7 meses (1), con o sin quimioterapia (1,25). Sin embargo, en oncología se valoran otros objetivos terapéuticos como la calidad de vida relacionada con la salud, el control de síntomas, los resultados indirectos, la seguridad y los resultados percibidos por los pacientes (54). Una prolongación modesta de la supervivencia y paliación de los síntomas con preservación de la calidad de vida es el objetivo real en estos pacientes, aunque en raros casos se ha reportado curación (27).…”
Section: Tratamientounclassified